(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Artificial intelligence now enables language education to create entirely new methods for teaching students how to speak. This study investigates how AI-based tools function as speaking development resources through their theoretical and analytical assessment of current research in applied linguistics educational technology and second language acquisition theory. The article demonstrates how educators can achieve better outcomes for their students through systematic implementation of artificial intelligence applications because these tools provide increased opportunities for authentic speaking practice and deliver customized feedback based on performance data which traditional educational methods cannot provide.